Challenges and supports for women conservation leaders. Issue 6 (25th April 2019) - Jones, Megan S.; Solomon, Jennifer
Abstract: Leadership and inclusivity are increasingly recognized as fundamental to conservation success, yet women's leadership within the conservation profession is understudied. This study identifies gender‐related challenges women conservation leaders experienced in their careers, and supports helping them advance. Using an intersectionality framing to identify intersections between gender, race/ethnicity, age, and leadership position, we conducted and analyzed semi‐structured interviews with 56 women leaders in conservation organizations across the United States. All interviewees reported experiencing or witnessing a gender‐related workplace challenge in at least one of six categories, and the vast majority reported encountering four or more of these challenges: salary inequality and difficulty negotiating, formal exclusion, informal exclusion, harassment and inadequate organizational response, assumptions of inadequacy, and assumptions of wrongness. Participants also experienced two categories of supports: structural supports and supportive relationships. Women's experiences varied based on age, race and ethnicity, and leadership position. Our results indicate more effort is needed to identify effective strategies for making conservation a more inclusive, empowering, and appealing profession in which to work.